PARCUKU: A RELIGIOUS RITUAL OF THE FAK-FAK COMMUNITY - Ade Yamin (Al-Albab, 2013)
Local Islam which is synonymous with the implementation of rituals is always interesting to discuss, either through free discussion or in the academic sphere, which will map out the speakers at both confronting and accommodating areas. Similarly, the Parcuku religious ritual of the Fak-Fak community gave rise to a wide range of supporting and opposing arguments for various reasons respectively. This paper provides a description of cultural activities of the Fak-fak people, which is closely related to the religion of Islam, in the face of the reality of the society which tends to be misunderstood by outsiders, or by Fak-fak people who have gained a new awareness in terms of religious (Islamic) teachings. The results of this research indicate that the Parcuku ritual, practiced by the community of Fak-fak, is a semi-religious ceremony with the main purpose of attempting to find a way of salvation for the people. Nevertheless, through the Parcuku ritual, a variety of positive things could be fostered in society such as cooperation, mutual help, and various other constructive social values that can be used in the realization of a harmonious society. Also, through a variety of ritual activities, we can be witness the characteristics of a community in its religious expression, and therefore it should not be a justification for blasphemies because it turns out that God is so great that He has a lot of names in the human mind. The next most important thing is that it appears there is only one God in the many religions on Earth. Keywords: Parcuku, religion, ritual, community, Fak-fak